2012
DOI: 10.1124/jpet.112.199497
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Metabolically Stabilized Angiotensin IV Analogs as Procognitive/Antidementia Agents

Abstract: Angiotensin IV (AngIV: VYIHPF)-related peptides have long been recognized as procognitive agents with potential as antidementia therapeutics. Their development as useful therapeutics, however, has been limited by physiochemical properties that make them susceptible to metabolic degradation and impermeable to gut and blood-brain barriers. A previous study demonstrated that the core structural information required to impart the procognitive activity of the AngIV analog, norleucine 1 -angiotensin IV, resides in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 42 publications
4
61
0
Order By: Relevance
“…In contrast, HA09 did not alter total spine density or morphology compared with the vehicle control. Given that previous studies have shown that the procognitive activity of a molecule in vivo correlates well with its in vitro ability to alter dendritic spine structure (Benoist et al, 2011;McCoy et al, 2013), these results suggest that HA08 may have cognitive enhancing effects.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In contrast, HA09 did not alter total spine density or morphology compared with the vehicle control. Given that previous studies have shown that the procognitive activity of a molecule in vivo correlates well with its in vitro ability to alter dendritic spine structure (Benoist et al, 2011;McCoy et al, 2013), these results suggest that HA08 may have cognitive enhancing effects.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have observed a correlation between the procognitive effects of Ang IV-derived peptides in rodents and their capacities to increase spine number and alter morphology (Benoist et al, 2011;McCoy et al, 2013). These data suggest that the positive impact of these peptides and peptidomimetics on cognition and dendritic spines might be attributed to a possible capacity to suppress the catalytic activity of the aminopeptidase IRAP.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…As for AT4, the identification of small but critically important peptide fragments [258] and their N-and C-terminal modifications led to the development of the selective AT4 agonist N-hexanoic-Tyr-Ile-(6) aminohexanoic amide. This molecule was sufficiently bloodbrain barrier permeable to have precognitive effects in Morris water maze performance [259]. Experiments using selective AT4 agonists are needed in the future to address their anti-convulsive actions.…”
Section: Angiotensinsmentioning
confidence: 99%
“…Nle 1 -AngIV, an often-employed AT 4 receptor agonist with demonstrated procognitive activity (Benoist et al, 2011), along with its metabolically stabilized and orally active derivative, N-hexanoic-tyrosine-isoleucine-(6) aminohexanoic amide (dihexa) (McCoy et al, 2013), were utilized to probe this question. Both agonists were found to potentiate the cellular actions of HGF.…”
Section: Introductionmentioning
confidence: 99%